Globalization and Islamic Indigenization in Southeast Asian Muslim Communities - Hoesterey, James B. (Islam Nusantara: Journal for the Study of Islamic History and Culture, 2022)
This study identifies the major challenges faced by Islam Nusantara in responding to political Islam in the contemporary world. It also aims to map the relationships and dynamics among three major currents of Islamic thought in Indonesia, traditional Islam, liberal Islam, and religious reformism, while explaining the role of Islam Nusantara in addressing contemporary crises through the intellectual legacy of Abdurrahman Wahid. The study employs a qualitative approach based on library research. Its analysis draws on historical scholarship and Indonesian Islamic thought in order to trace the genealogies and transmission of reformist ideas, the development of liberal Islamic discourse, and the responses articulated within traditionalist Islam. The findings show that Islamic reformism in Indonesia was shaped through the influence of major intellectual centers in the Middle East, including Mecca, Medina, and Cairo. Traditional Islam, by contrast, developed as a local Islamic cultural inheritance that emphasizes continuity of tradition and religious authority. Liberal Islam emerged through engagement with modern Muslim thinkers, including Fazlur Rahman. The study further demonstrates that the convergence between reformism and traditionalism has remained dynamic, involving ongoing negotiation, adaptation, and sustained forms of resistance, all of which have contributed to shaping the configuration of Indonesian Islam in the contemporary landscape. This article contributes to scholarship on the history of Indonesian Islamic thought by affirming Islam Nusantara as a conceptual framework for strengthening pluralism, mitigating the polarization produced by political Islam, and sustaining cultural-intellectual strategies for addressing current socio-religious crises.